2011
DOI: 10.21082/ijas.v12n1.2011.p1-8
|View full text |Cite
|
Sign up to set email alerts
|

Genesis and Properties of Peat at Toba Highland Area of North Sumatra

Abstract: In Indonesia, peat soil in the highland area is only found in the plateau of Toba Highland, North Sumatra, and its morphologi-cal, physical, and chemical properties have been studied. Four profiles of peat soil were made in the field and eighteen samples were taken and analyzed in laboratory. Most of the properties of highland peat were similar with lowland peat. The differences were in their Al saturation, P retention, and andic soil properties. High Al saturation was resulted from weathering of primary miner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The high NaF-pH and low H2O-pH also point to the Andisol origin of this soil. Prasetyo et al (2009) argued that the low allophane in soils was due to the development of the soil and the desilification process so that the allophane content was reduced and formed halloysite hydrate crystalline minerals. The halloysite of 10 Å is found only on the Bw2 horizon in soil profile 1, while the halloysite with 7 Å diffraction peak is the one found in the Ah horizons of soil profiles 1 and 2.…”
Section: Clay Mineralogymentioning
confidence: 99%
See 1 more Smart Citation
“…The high NaF-pH and low H2O-pH also point to the Andisol origin of this soil. Prasetyo et al (2009) argued that the low allophane in soils was due to the development of the soil and the desilification process so that the allophane content was reduced and formed halloysite hydrate crystalline minerals. The halloysite of 10 Å is found only on the Bw2 horizon in soil profile 1, while the halloysite with 7 Å diffraction peak is the one found in the Ah horizons of soil profiles 1 and 2.…”
Section: Clay Mineralogymentioning
confidence: 99%
“…Cristobalite is a silica (SiO2) mineral member, while gibbsite is an aluminum hydroxide mineral (Al(OH3)). Gibbsite can be formed directly through the weathering of primary minerals (Wada and Aomine, 1966;Prasetyo et al, 2009). Cristobalite can be known through XRD analysis with diffraction peaks of 4.26 and 3.34 Å. Gibbsite displays a diffraction peak of 4.82 Å. Interestingly, illite (10 Å) is present in few to moderate amounts in all soil profiles and tends to increase with soil depth.…”
Section: Naalsi3o8 (Albite) + 2h2co3 + 9h2omentioning
confidence: 99%
“…This was presumably because it is influenced by the parent material in each soil unit (pedon). The nature and characterization of soils were shown to be strongly influenced by the parent material (Prasetyo, 2007;Suharta, 2007). The analysis results showed that the soil erosion rate of maize plantings was dominated by moderate, heavy, and very heavy categories, with an area percentage of 80.14%, as shown in Table 5 and Figure 2.…”
Section: Land Characteristics and Land Degraded By Soil Erosionmentioning
confidence: 99%